2014
DOI: 10.1136/bmjopen-2014-005283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on anthropometric measures and serum lipids in older individuals: a systematic review and meta-analysis

Abstract: ObjectivesOverweight and obesity are increasing in individuals over age 60 years. This systematic review quantifies the effect of exercise on body mass index (BMI), waist circumference (WC) and lipids in overweight and obese individuals over the age of 60 years.SettingsNine randomised controlled trials conducted in Brazil, Great Britain, Iceland, Japan and the USA compared aerobic and/or resistance exercise with a control group.ParticipantsFinal analysis reviewed 1166 participants over the age of 60 years for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…This is supported by RCTs that demonstrate that endurance training and strength training reduce blood pressure [ 21 23 ]. In addition, endurance training also reduces fat mass and abdominal circumference [ 22 , 24 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by RCTs that demonstrate that endurance training and strength training reduce blood pressure [ 21 23 ]. In addition, endurance training also reduces fat mass and abdominal circumference [ 22 , 24 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among 8 reports of systematic review and metaanalysis of RCTs with comparison of exercise and non-exercise control including Japanese participants and were published after 2,000, significant decreases in LDL-C and TG levels were reported in two articles, respectively. Six reported a significant increase in HDL-C levels, which was the most frequently observed effect of exercise on serum lipids 577 , 607 613 ) . A meta-analysis of 25 RCTs that compared aerobic exercise for training periods of at least 15 minutes for ≥ 8 weeks with nonexercise control reported that exercise therapy significantly increased the HDL-C levels 612 ) .…”
Section: Comprehensive Risk Managementmentioning
confidence: 96%
“…However, previous studies were limited by their relatively small sample size, short follow-up period, single hospital data and lack consideration of effect of exercise on serum lipids. A meta-analysis of 1,166 participants aged over 60 years found exercise enables to improve anthropometric measures (i.e., body mass index and waist circumference), but this meta-analysis suggested the effect of exercise on serum lipids remains unclear 12 .…”
Section: Introductionmentioning
confidence: 89%